Patients receiving a high burden of antibiotics in the community in Spain: a cross‐sectional study - Rocío Fernández‐Urrusuno; Carmen Marina Meseguer Barros; Sonia Anaya‐Ordóñez; Yolanda Borrego Izquierdo; María Jesús Lallana‐Álvarez; Rosa Madridejos; Esther Marco Tejón; Raquel Prieto Sánchez; Olatz Pérez Rodríguez; María García Gil; Belén Escudero Vilaplana; Genma M. Silva Riádigos; et al. (Wiley, 2021)
Abstract Some patients in the community receive a high burden of antibiotics. We aimed at describing the characteristics of these patients, antibiotics used, and conditions for which they received antibiotics. We carried out a cross‐sectional study. Setting: Thirty Health Primary Care Areas from 12 regions in Spain, covering 5,960,191 inhabitants. Patients having at least 30 packages of antibacterials for systemic use dispensed in 2017 were considered. Main outcome measures: Prevalence of antibiotic use, conditions for which antibiotics were prescribed, clinical characteristics of patients, comorbidities, concomitant treatments, and microbiological isolates. Patient's average age was 70 years; 52% were men; 60% smokers/ex‐smokers; 54% obese. Overall, 93% of patients had, at least, one chronic condition, and four comorbidities on average. Most common comorbidities were cardiovascular and/or hypertension (67%), respiratory diseases (62%), neurological/mental conditions (32%), diabetes (23%), and urological diseases (21%); 29% were immunosuppressed, 10% were dead at the time of data collection. Patients received three antibiotic treatments per year, mainly fluoroquinolones (28%), macrolides (21%), penicillins (19%), or cephalosporins (12%). Most frequently treated conditions were lower respiratory tract (infections or prophylaxis) (48%), urinary (27%), and skin/soft tissue infections (11%). Thirty‐five percent have been guided by a microbiological diagnosis, being Pseudomonas aeruginosa (30%) and Escherichia coli (16%) the most frequent isolates. In conclusion, high antibiotic consumers in the community were basically elder, with multimorbidity and polymedication. They frequently received broad‐spectrum antibiotics for long periods of time. The approach to infections in high consumers should be differentiated from healthy patients receiving antibiotics occasionally.